Role of Leaders as Agents of Negotiation for Counterbalancing Cultural Dissonance in the Middle East and North Africa Region - Karacay, Gaye; Bayraktar, Secil; Kabasakal, Hayat; Dastmalchian, Ali (Elsevier BV, 2019)
Abstract This study provides a unique perspective in the field of cross-cultural management by exploring the relationship between “cultural dissonance”—the gap between cultural values and actual practice—and effective leadership attributes in the Middle East and North Africa (MENA) region. Incorporating cultural dissonance into implicit leadership theory, the study uses measurements of dissonance on nine cultural dimensions to identify particular leadership preferences in seven MENA countries. The overall findings suggest that societies prefer leaders who counterbalance cultural dissonance by allowing space for negotiations by members of society to reduce disparities between cultural values—“the way things should be”—and actual practices—“the way things are.” The greater the disparity between cultural values and practices, the greater the citizens' desire that leaders act as agents of change by creating space for negotiation.